2004
DOI: 10.1094/mpmi.2004.17.4.394
|View full text |Cite
|
Sign up to set email alerts
|

The Avr1b Locus of Phytophthora sojae Encodes an Elicitor and a Regulator Required for Avirulence on Soybean Plants Carrying Resistance Gene Rps1b

Abstract: We have used map-based approaches to clone a locus containing two genes, Avr1b-1 and Avr1b-2, required for avirulence of the oomycete pathogen Phytophthora sojae (Kaufmann & Gerdemann) on soybean plants carrying resistance gene Rps1b. Avr1b-1 was localized to a single 60-kb bacterial artificial chromosome (BAC) clone by fine-structure genetic mapping. Avr1b-1 was localized within the 60-kb region by identification of an mRNA that is expressed in a race-specific and infection-specific manner and that encodes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
295
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 311 publications
(308 citation statements)
references
References 58 publications
10
295
3
Order By: Relevance
“…confirmed the root cell entry experiments of Dou et al (2008) using full length Avr1b protein and using more specific mutations of RXLR2 (qFLR) that agreed with results of bombardment experiments of Dou et al (2008). Furthermore, validating an observation of Shan et al (2004), showed that full length Avr1b protein could trigger cell death on leaves containing the Rps1b resistance gene, but not on leaves lacking Rps1b. The ability to trigger Rps1b-mediated cell death was abolished by the qFLR mutation and a dEER motif mutation, consistent with RxLR-dependent entry into soybean cells.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…confirmed the root cell entry experiments of Dou et al (2008) using full length Avr1b protein and using more specific mutations of RXLR2 (qFLR) that agreed with results of bombardment experiments of Dou et al (2008). Furthermore, validating an observation of Shan et al (2004), showed that full length Avr1b protein could trigger cell death on leaves containing the Rps1b resistance gene, but not on leaves lacking Rps1b. The ability to trigger Rps1b-mediated cell death was abolished by the qFLR mutation and a dEER motif mutation, consistent with RxLR-dependent entry into soybean cells.…”
supporting
confidence: 77%
“…Tyler's lab at the University of California, Davis (Shan et al 2004) that were later replicated in Kale and associates (2010). Lab member B. Gu visited the Tyler lab at Virginia Tech where he carried out numerous root cell entry experiments including replicates of those described in Kale and associates (2010), and particularly experiments with Avr1bNt-GFP.…”
Section: W Shan Northwest a And F University China The Shan Lab Stumentioning
confidence: 92%
“…c Noks1 was derived from an oospore of Noco2 (used in Botella et al, 1998), and its interaction phenotype matches that of Noco2 (Holub et al, 1994). oomycete avirulence genes (Allen et al, 2004;Shan et al, 2004 Figure 1). All alleles encoded full-length proteins, and none displayed substitutions rendering them obvious null alleles.…”
Section: A Candidate For Atr1 Nd Encodes a Polymorphic Secreted Proteinmentioning
confidence: 99%
“…ATR13 from H. parasitica was cloned by isolating an in planta-expressed sequence that cosegregated with and encoded ATR13 (Allen et al, 2004). By contrast, map-based cloning approaches resulted in the identification of Avr1b-1 from Phytophthora sojae (Shan et al, 2004) and AvrL567 from Melampsora lini (Dodds et al, 2004). All three genes are predicted to encode proteins with N-terminal signal peptides, suggesting that they are secreted from the pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation